Internalisasi Kitab Washoya Al-Abaa Lil Abnaa dalam Membentuk Akhlak Santri - Arifin, Pipin Hasan; Darma, Surya Hadi; Wulandari, Dyah (Jurnal Riset Agama, 2023)
This study aims to discuss the internalization of the Washoya Al-Abaa Lil Abnaa book and its role in shaping morals in students. The method used in this research is descriptive qualitative with data collection techniques through observation and interviews at Ar-Rohmah Islamic Boarding School Plered Purwakarta. The data analysis techniques used are triangulation techniques and source triangulation. The results showed that the book of Washoya Al-Abaa Lil Abnaa is a book that contains the will of a teacher to his students regarding morals. The learning process of the Washoya book at Ar-Rohmah Islamic Boarding School is carried out with learning stages which are preceded by prayer activities, introspection to the author of the book followed by recitation, then in the process of learning the Washoya book using the bandongan and lecture methods. The internalization of moral values through the Washoya Al-Abaa Lil Abnaa Book at the Ar-Rohmah Islamic Boarding School is moral to Allah SWT, moral to oneself, moral to fellow humans, and moral to the environment.